Tuning the Optoelectronic Properties of Nonfullerene Electron Acceptors. Issue 6 (21st October 2014) - Fang, Yuan; Pandey, Ajay K.; Lyons, Dani M.; Shaw, Paul E.; Watkins, Scott E.; Burn, Paul L.; Lo, Shih‐Chun; Meredith, Paul
Abstract: Broad spectral coverage over the solar spectrum is necessary for photovoltaic technologies and is a focus for organic solar cells. We report a series of small‐molecule, nonfullerene electron acceptors containing the [(benzo[ c ][1, 2, 5]thiadiazol‐4‐yl)methylene]malononitrile unit as a high electron affinity component. The optoelectronic properties of these molecules were fine‐tuned with the objective of attaining strong absorption at longer wavelengths by changing the low‐ionization‐potential moiety. The electron‐accepting function of these materials was investigated with poly(3‐ n ‐hexylthiophene) (P3HT) as a standard electron donor. Significant photocurrent generation in the near infrared region, with an external quantum yield reaching as high as 22 % at 700 nm and an onset >800 nm was achieved. The results support efficient hole transfer to P3HT taking place after light absorption by the acceptor molecules. A Channel II‐dominated power conversion efficiency of up to 1.5 % was, thus, achieved. Abstract : New acceptors: A series of small‐molecule, nonfullerene electron acceptors containing the [(benzo[ c ][1, 2, 5]thiadiazol‐4‐yl)methylene]malononitrile unit is designed to possess different absorption profiles and optical gaps (see picture). When poly(3‐ n ‐hexylthiophene) (P3HT) is used as the standard electron donor, significant photocurrent generation in the near infrared region, with an external quantum yield reaching as high as 22 % at 700 nm and an onset >800 nm are achieved.